Entrepreneurial Soul in Primary School Students: Qualitative approach - Sundahry, Sundahry; Fauziah, Fauziah; Subhanadri, Subhanadri; Firman, Firman (Journal of Economics Education and Entrepreneurship, 2024)
Introducing an entrepreneurial spirit to elementary school students is an important role very important in increasing their independence and has many benefits very good and will have an impact on his future. How to what is the right way to build an entrepreneurial spirit for elementary school students and what method appropriately applied. Meanwhile introducing and cultivating an entrepreneurial spirit cannot be done instantly for elementary school students for that and the role This teacher really supports the formation of a person's character entrepreneurship in the future. This research uses a qualitative approach with descriptive explanatory analytical studies, this method describes the facts the importance of building an entrepreneurial spirit for elementary school students. The purpose of this research to examine the benefits of building an entrepreneurial spirit in elementary school students through the development of formal education and research this is only limited instilling an entrepreneurial spirit in the family and immediate environment. Through Entrepreneurship training for elementary school students is to foster a sense of be confident, independent and be a person who has high creativity so that they become more productive when they grow up.